Analysis of Digital Literacy in Biology Learning at SMAN 3 Batu Ampar - Amboni; Adi Pasah Kahar; Hanum Mukti Rahayu (Jurnal Report of Biological Education, 2021)
Background: Information technology has offered various conveniences in biology learning, students can learn more flexibly and are not hindered by the limitations of space and time, so it must be balanced with digital literacy. This study aims to determine the level of digital literacy of students in biology learning in class X SMAN 3 Batu Ampar. Method: This study used descriptive qualitative method. The research subjects were students of class X SMAN 3 Batu Ampar. Data collection techniques using indirect communication and observation. Collecting data using a questionnaire sheet and an observation sheet. The data analysis technique used is descriptive statistical analysis. Results: The results show that the level of digital literacy of students on the basic standard indicators of computer use is moderate (51%), while the basic internet standard indicators are moderate (50%), the basic standard indicators for the Windows operating system are low (43%), and the basic standard indicators for e-mail is low (48%). Conclusion: The level of digital literacy of class X students of SMAN 3 Batu Ampar in biology learning is classified as moderate. Despite the lack of facilities owned by some students, students have been able to use the internet to complete tasks in biology learning.